Downstream, Good Mining Practices, Reclamation and Post-Mining: Policy and Law Enforcement in Indonesia - Sudaryat, Sudaryat (Jurnal Ius Constituendum, 2025)
This research aims to find out and see the connection between operational patterns in mineral and coal mining activities in Indonesia, downstream policies, as well as reclamation and post-mining implementation. Mining activities cause negative impacts in the form of serious environmental damage which occurs in almost all mining areas in Indonesia. From a regulatory perspective, mining companies and mining service companies are obliged to implement good mining principles with administrative sanctions for those who violate them, mining companies are obliged to carry out downstream within the country so as to provide added value and expand employment opportunities, mining companies are also obliged to carry out reclamation and post-mining at a high level. higher. 100% success. Using normative juridical research methods and qualitative juridical analysis, it is known that the operational cooperation pattern is not appropriate to apply because, in the operational cooperation agreement, the position of the mining company and the mining service company is equal so that the mining service company does not carry out good mining activities, the mining company does not have control over this and In fact, 70% of environmental damage in Indonesia is due to mining operations, mineral, and coal downstream policies are carried out inconsistently so that it is less than optimal in increasing the added value of minerals and coal and there are legal loopholes in opening up reclamation in other forms, making the success rate of reclamation and post-mining of ex-mining excavated flat. the average is less than achieved 100% success.